1993
DOI: 10.1128/jb.175.22.7468-7470.1993
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the three rRNA operons on the updated genomic map of Campylobacter jejuni TGH9011 (ATCC 43431)

Abstract: The three rRNA gene loci of Campylobacter jejuni TGH9011 (ATCC 43431) were cloned. All three rRNA operons were shown to possess a contiguous 16S-23S structure and contain intercistronic tRNA(Ala) and tRNA(Ile). The three RNA operons and additional 14 genetic markers were mapped in the updated genomic map of C. jejuni TGH9011, which now has a total of 24 genetic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…Southern hybridizations were performed to determine the presence of the relevant gene in Campylobacter strains. The hippuricase gene has already been localized (16) on the physical map of C. jejuni TGH9011 (18) and was shown to be present in single copy (data not shown). The type strain of C. jejuni contains a 19-kb ClaI genomic DNA band and a 2.1-kb HindIII genomic DNA band which hybridize to the hippuricase probe ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Southern hybridizations were performed to determine the presence of the relevant gene in Campylobacter strains. The hippuricase gene has already been localized (16) on the physical map of C. jejuni TGH9011 (18) and was shown to be present in single copy (data not shown). The type strain of C. jejuni contains a 19-kb ClaI genomic DNA band and a 2.1-kb HindIII genomic DNA band which hybridize to the hippuricase probe ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the characteristic continuous 16S-23S (eu)bacterial rRNA operon structure seen in E. coli (35), several studies have suggested that in at least one of the three C. jejuni rRNA operons, the 16S and 23S genes are located separately (23,27,37,57). However, recent fine mapping of the three rRNA gene loci of one of these C. jejuni strains has shown that all three operons possess a contiguous 16S-23S structure (25). The sequence and organization of one of these contiguous rRNA operons has recently been described (GenBank accession number Z29326).…”
mentioning
confidence: 93%
“…This allowed us to identify strain-specific diversity which might be involved in virulence potential. These two C. jejuni strains differ by several phenotypic and genotypic features: (i) their Penner serotype: ATCC 43431 (TGH 9011) is Penner serotype O:3, while NCTC 11168 is Penner serotype O:2 (49); (ii) their invasion ability: NCTC 11168 is poorly invasive (3), while ATCC 43431 appears to be highly invasive (17,18); (iii) their genome size: the genome of ATCC 43431 appears to be larger than that of NCTC 11168 (21,34); and (iv) their gene order: gene positions seem to differ considerably between the two strains (21,22,34). Since invasion ability has been shown to correlate with epidemiological outcomes (10), the genes unique to ATCC 43431 will provide a valuable resource to dissect the C. jejuni features that affect pathogenic potential.…”
mentioning
confidence: 99%